THE STUDY OF LANGUAGE ELEMENTS IN THE POETRY OF ABDULLA ORIPOV - Aliyeva Lola Khomidovna (Bright Mind Publishing, 2025)
This article presents a linguistic analysis of the poetic works of Abdulla Oripov—one of the most prominent figures in modern Uzbek literature. Special attention is given to the application of linguistic elements in his poetry, their aesthetic and stylistic weight, and the harmony between poetic syntax and artistic expression. The paper examines Oripov’s unique poetic style, his rich lexical resources, his strategic use of grammatical tools, and the expressive power of linguistic devices within the poetic structure. These aspects are analyzed in light of both theoretical linguistics and literary stylistics.
Keywords: Abdulla Oripov, poetic language, linguistic elements, poetic syntax, stylistics, figurative language, expressiveness.